USING LIST GROUP LABEL (LGL) STRATEGY TO IMPROVE VOCABULARY ACHIEVEMENT OF THE SEVENTH GRADE STUDENTS OF SMP NEGERI 20 PALU - Risfiani, Andira Risfiani; Mertosono, Sudarkam R; Munir, Syahrul; Maf’ulah, Maf’ulah (e-Journal of ELTS (English Language Teaching Society), 2024)
The objective of this research is to figure out whether or not the using of List Group Label (LGL) strategy can improve vocabulary achievement of the seventh grade students of SMP Negeri 20 Palu. The population of this research are the seventh grade students of SMP Negeri 20 Palu, the sample was VII D as experimental class and VII A as control class. The research applied quantitative method. The instrument of the data collection were pre-test and post-test. Those data were analyzed statistically. The pre-test was in low level and the post-test was in high level. The pre-test was in low level because the students have difficulties in vocabulary related to hobbies. However, the post-test that in high level because of the List Group Label (LGL) strategy can improve vocabulary achievement. The result of the data analysis shows that the t-counted was greater than the t-table. In conclusion, the use of List Group Label (LGL) strategy can improve vocabulary achievement of the seventh-grade students of SMP Negeri 20 Palu.